META ANALYSIS: EFFECTIVENESS OF GOOGLE CLASSROOM, MOODLE IN BLENDED LEARNING AS VOCATIONAL LEARNING MEDIA IN INDONESIA - adi andikos (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
The purpose of this research is to find out the effectiveness of blended learning on the google classroom platform and moodle as a medium of vocational school in Indonesia. The effectiveness assessment is examined from several previous findings or studies. This research uses meta-analysis methods, in accordance with the application of research topics, and conducts research on several research journals taken purposively or directedly. The research journal used is in the last five years (2015-2020) derived from a google scholar database of 16 journals. Analysis of the data used is qualitatively descriptive. From the meta analysis done shows that the objectives that are often studied are impact or influence and or effectiveness 56%, the most commonly used design is the experiment 63%, the most commonly used data analysis is observation by 53%. Data analysis that is often done by research is t-test 50%. In SMK google classroom platform is used more often 81% than moodle platform 19%, and blended learning research through google classroom platform, moodle is more effective to improve learning results by 65%. Meta analysis of student learning outcomes, motivation and self-reliance were the most frequently reviewed from the 16 journals.